Exploring communication challenges due to language and cultural diversity on South African construction sites - Emuze, Fidelis; James, Matthew (University of the Free State, 2013)
Communication can be traced to, among others, an individual’s language and cultural background. These aspects play a fundamental role in ensuring effective communication. Literature surveys show that language and culture have contributed to ineffective communication, giving rise to a wide range of problems in the construction industry. These problems include an increase in rework and poor product quality, and low employee morale. Given the multicultural environment in which construction activities occur in South Africa, communication can potentially dictate the extent of project performance. In order to explore the impact of this phenomenon, a survey was undertaken among general workers and site managers employed by five general contractors (GCs) in the Eastern Cape province of South Africa. Salient findings include that communication problems occur on construction sites due to language and cultural diversity-related barriers; site managers are generally effective at communicating; the South African workforce is diversely cultured, which potentially leads to misunderstandings on sites, and language barriers between site management and site workers impede performance improvement.

Kommunikasie kan teruggevoer word na, onder andere, ‘n individu se taal en kulturele agtergrond. Hierdie aspekte speel ‘n belangrike rol in effektiewe kommunikasie. Literatuuroorsigte toon dat taal en kultuur bygedra het tot oneffektiewe kommunikasie, wat aanleiding gee tot ‘n wye verskeidenheid probleme in die konstruksiebedryf. Hierdie probleme sluit in ‘n toename in werkherhaling en swak produkkwaliteit asook lae werknemersmoraal. Gegewe die multikulturele omgewing waarbinne konstruksie aktiwiteite in Suid-Afrika voorkom, kan kommunikasie potensieel die omvang van projekprestasie voorspel. Ten einde die impak van hierdie verskynsel te voorspel, is ‘n opname gedoen onder algemene werkers en die bestuurders werksaam by vyf algemene kontrakteurs in die Oos-Kaap provinsie van Suid-Afrika. Belangrike bevindinge sluit in dat kommunikasieprobleme plaasvind op konstruksieterreine as gevolg van taal- en kulturele verskeidenheid-verwante hindernisse; terreinbestuurders kommunikeer in die algemeen effektief; die Suid-Afrikaanse werkerskorps kom uit verskeie kulturele agtergronde wat potensieel tot misverstande op bouterreine mag lei, en taalgrense tussen terreinbestuurders en -werkers hinder prestasieverbetering.
Keywords: Communication; Construction; Site managers; Site workers